The Influence of Unconscious Perceptual Processing on Decision-Making: A New Perspective From Cognitive Neuroscience Applied to Generation Z - Sutil-Martín, Dolores Lucía; Rienda-Gómez, Juan José (Frontiers in Psychology, 2020)
Cognitive neuroscience and its applied developments have revolutionized marketing. With advances in neuroscientific techniques, marketing has needed to refocus toward understanding issues like the area of the brain that should be stimulated to transform the consumer’s intention to purchase into a real decision, how information is processed when making a decision, and how personality traits affect the purchase decision. Neuroscience has opened the door to the consumer’s brain. For many years, scientists have investigated the role of subliminal messages in marketing, with their findings generating a significant controversy. Many have shown that making sound decisions based on intuition rather than conscious reasoning is more common than previously thought. In fact, many studies have shown that sound intuitive decision-making depends on the association of the subliminal messages of a given situation with the limbic brain structures formed. Scientists have concluded that the brain does not consciously need to know contextual information to learn the value of this information and make the necessary linkages to make productive decisions. In this study, we consider whether unconscious perceptual processing influences decision-making and explore the influence of aspects of personality that are related to unconscious processing, such as the degree of neuroticism, extroversion, and gender of the individual, applied to the demographic cohort Generation Z, distinguishing between whether the stimuli are verbal or pictorial. The backward masking visual paradigm has been used to assess unconscious perceptual processing. To test these processes, a set of ANOVA models and logistic regressions were run where the dependent variable is whether the people perceived the stimuli or not and the independent variables were gender, the form of the stimuli (pictorial or verbal), and the personality traits extroversion, introversion, and neuroticism. The results suggest that verbal stimuli work better than pictorial stimuli, although a possible explanation is that the pictures require modification to be more effective. In the case of verbal stimuli, gender and level of neuroticism are found to be important variables that influence unconscious perceptual decision-making processes. Specifically, a female with a high level of neuroticism shows greater permeability in its unconscious perceptual processes.